Medicine OnLine – an interactive World Wide Web service created for oncologists - Mackiewicz, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
Among internet sites devoted to oncology, there is an interesting service – Medicine OnLine at http: //www. meds.com, created by UltiTech, Inc. Construction of this database begun in 1995 and the internet service started on May 15, 1995. For the past four years www.meds.com has been awarded with several internet prizes for the best medical homepage. The excellently prepared database offers a lot of information for oncology professionals and cancer patients as well. The most important element of this service is a virtual system for planing chemotherapy.